GPER/GPR30 knockout mice: effects of GPER on metabolism - Sharma, Geetanjali (Methods Mol Biol, 2016)
Endogenous estrogens, predominantly 17β-estradiol (E2), mediate various very diverse effects throughout the body in both normal physiology and disease. Actions include development (including puberty) and reproduction as well as additional effects throughout life in the metabolic, endocrine, musculoskeletal, nervous, cardiovascular and immune systems. The actions of E2 have traditionally been attributed to the classical nuclear estrogen receptors (ERα and ERβ) that largely mediate transcriptional/genomic activities. However, more recently the G protein-coupled estrogen receptor GPER/GPR30 has become recognized as an essential mediator of certain, and particularly rapid, signaling events in response to E2. Murine genetic knockout (KO) models represent an important approach to understand the mechanisms of E2 action in physiology and disease. Studies of GPER KO mice over the last years have revealed functions for GPER in the regulation of obesity, insulin resistance and glucose intolerance, among other areas of (patho)physiology. This chapter focuses on methods for the evaluation of metabolic parameters in vivo and ex vivo with an emphasis on glucose homeostasis and metabolism through the use of glucose and insulin tolerance tests, pancreatic islet and adipocyte isolation and characterization.